Prenatal determinants of physical activity and cardiorespiratory fitness in adolescence - Northern Finland Birth Cohort 1986 study - Tikanmaki, Marjaana; Tammelin, Tuija; Vaarasmaki, Marja; Sipola-Leppänen, Marika; Miettola, Satu; Pouta, Anneli; Jarvelin, Marjo-Riitta; Kajantie, Eero (BMC Public Health, 2017)
Background: Lower levels of physical activity and cardiorespiratory fitness are key risk factors of chronic adult diseases. Physical activity and cardiorespiratory fitness are predicted by birth weight, but the underlying parental and pregnancy-related factors remain largely unknown. We examined how prenatal determinants are associated with physical activity and cardiorespiratory fitness in adolescence. Methods: Of the 16-year-old members of the population-based Northern Finland Birth Cohort 1986 (NFBC 1986), 6682 singletons with no major physical disability reported their amount of physical activity outside school hours, and 4706 completed a submaximal cycle ergometer test assessing cardiorespiratory fitness. Physical activity was expressed as metabolic equivalent hours per week (METh/week) and cardiorespiratory fitness as peak oxygen uptake (ml center dot kg(-1)center dot min(-1)). Prenatal determinants included birth weight, length of gestation, mother's and father's body mass index (BMI), maternal gestational diabetes mellitus (GDM), and maternal hypertension and smoking during pregnancy. Data were analyzed by multiple linear regression. Results: A higher birth weight and longer length of gestation predicted lower levels of physical activity and cardiorespiratory fitness at 16 years, although the association between length of gestation and physical activity was inverse U-shaped. Mother's or father's overweight or obesity before pregnancy were associated with lower levels of their offspring's physical activity and fitness in adolescence. Adjusting for maternal pregnancy disorders and the adolescent's own BMI attenuated the associations with the mother's but not the father's overweight/obesity. Furthermore, maternal GDM predicted lower cardiorespiratory fitness. Conclusions: A high birth weight and parental overweight/obesity are associated with lower levels of both physical activity and cardiorespiratory fitness in adolescence, while maternal GDM and longer length of gestation are associated with lower ...